Topological Transitivity of Algebraically Recurrent Sets - Shoptrajanov, Martin (Sarajevo Journal of Mathematics, 2025)
In this paper, we will discuss the connection between topological transitivity and recurrence of \( G \)-flows acting on a compact metric space \( X \). We will prove that the \( T T \)-property of the set of all algebraically recurrent points \( AR(φ) \) implies chain recurrent properties of the whole space and hence improve some of the results from [6].